Queer Isn’t a Choice! Queer Is My Family! - Baer, Pamela (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
This article reflects on the way that young people with LGBTQ2S+ parents engaged in the writing of an original song as a form of gender and sexual diversity education during an applied theatre research project. The creative work was self-revelatory, deeply personal, and created a powerful space for both self-exploration and youth-led advocacy. Participants believed that queer is to be celebrated, embraced, and owned. Not as a marginal identity that needs to be questioned and explained, but as an embodied site of emergence and becoming. The song that was written during this workshop celebrates unique family formations while also suggesting that everyone is different in their own way. In doing so, songwriting as affective practice engaged participants in a subversive and empowering reordering of their world. The emergence of new possibilities materialized by centring the stories of, by, and for youth participants as we navigated the tensions between authorship, aesthetics, and pedagogy.